Helicobacter pylori vacA transcription is genetically-determined and stratifies the level of human gastric inflammation and atrophy - Sinnett, Charlotte G.; Letley, Darren P.; Narayan, Geetha L.; Patel, Sapna Rohitbhai; Hussein, Nawfal Rasheed; Zaitoun, Abed M.; Robinson, Karen; Atherton, John C. (BMJ Publishing Group Ltd, 2016)
Aims